Islamic Religious School as an alternative education institution in the Global Era: A Bibliometric and thematic analysis - Mohd Yahya bin Mohd Hussin, Fidlizan bin Muhammad, Azila binti Abdul Razak (Tanjung Malim, 2024)
Islamic Religious School as an alternative education institution in the Global Era: A Bibliometric and thematic analysis by Mohd Yahya bin Mohd Hussin, Fidlizan bin Muhammad, Azila binti Abdul Razak